Clyde Monster - Crowe, Robert L.; Chorao, Kay. (New York : Dutton, 1976)
A young monster is afraid of the dark because he believes that a person may be lurking under the bed or in a corner.
Children's Catalog (Wilson)
Elementary School Library Collection (Bro-Dart)
SLJ Best Book
2.0
K-3
Keywords: Monsters -- Fiction; Night -- Fiction; Monsters -- Fiction; Night -- Fiction